Metamorphism, melting, and channel flow in the Greater Himalayan Sequence and Makalu leucogranite: Constraints from thermobarometry, metamorphic modeling, and U-Pb geochronology - Streule, M; Searle, M; Waters, D; Horstwood, M (2010)
The Makalu leucogranite in the eastern Nepal Himalaya is a multiphase intrusion forming the structurally highest foliation-parallel sheets along the top of the Greater Himalayan Sequence. It is part of a chain of Miocene granites seen continuously along the length of the Himalaya and is composed of Grt + Tur + Ms Bt leucogranites but, unlike most other Himalayan granites, also locally contains coarse-grained cordierite. The cordierite-bearing leucogranite intrudes through and overlies lower sheets of "normal" tourmaline granites and represents the most recent phase of magmatism. Cross-cutting feeder dykes channelled magma up from the source region within the sillimanite grade Barun gneiss to the upper sheet. Petrology shows evidence for muscovite dehydration melting (∼700°C) in the upper part of the Barun gneiss of the Greater Himalayan Sequence, which retains biotite, indicating that melting temperatures did not exceed 800C. Secondary cordierite around garnet in these gneisses and the presence of cordierite in leucogranites record the last low-pressure decompression phase of melting. P-T determinations detail peak sillimanite grade metamorphism at 713°C/5.9 kbar, with a secondary cordierite overprint at 618°C/2.1 kbar; this P-T transition lies wholly within the modeled melt field. Monazite, zircon, and xenotime geochronology links the metamorphism and the different leucogranites. The main phase of leucogranite production occurred from 24 to 21 Ma, while the most recent melting occurred in the cordierite leucogranite and the migmatitic Barun gneisses at 15.6 ± 0.2 and 16.0 ± 0.6 Ma, respectively. Pseudosections for the migmatitic Barun gneiss and cordierite leucogranite show conditions of final cordierite bearing melt crystallization at approximately 4 kbar and 700°C and two main phases of melting: one associated with muscovite dehydration melting and one associated with formation of cordierite. These data support the channel flow model for the Greater Himalaya where decompression melting was coeval with southward ductile extrusion of a partially molten layer of middle crust during the Early and Middle Miocene. Copyright 2010 by the American Geophysical Union.